Overarching Values in Cultural Studies Perspective - Kot, Władysław (Sensus Historiae, 2024)
In this text—with the intention of elucidating the content of certain terms used in axiology, employed by me in philosophy classes within the field of pedagogy, and additionally within the framework of Jerzy Kmita’s initially adopted socio-regulatory concept of culture—I focus on a distinguished group of overarching values, essential in the practice of social communication for the “strengthening” and valorization of specific actions and their outcomes. Particularly crucial in the process of education at all levels are worldview values, including those deemed “ultimate.”